DIGITAL PLATFORMS IN ELT LEARNING AS THE TOOL FOR YOUNG LEARNERS - Sari, Ima Frafika (Indonesian EFL Journal, 2022)
The goal of this study is to uncover: the use of digital platforms in English language instruction for young learners. It's a type of qualitative study aiming at showing the use of digital platforms as a tool for young learners in ELT Learners. Because there is still a scarcity of research on digital platforms in the English language as a foundation for young learners, this study is essential. The following is a summary of the study findings: First, the teacher constantly listens to and observes the pupils, allowing them to check their spoken language, provide immediate or delayed feedback, and encourage active involvement and engagement in the speaking activities. Speaking looks to be the easiest of the four basic language abilities to teach online. The teacher monitors the pupils' spoken language, provides immediate or delayed feedback, and encourages active involvement and engagement with the speaking exercises. Second, Edmodo, SeeSaw, Sway, Class Dojo, and Show My Homework are examples of online learning programs that allow young learners to apply English language learning effectively. Keywords: digital platforms; ELT; ELT learning; young learners.